2019
DOI: 10.1111/jdv.15982
|View full text |Cite
|
Sign up to set email alerts
|

Split‐thickness skin grafts obtained from adjacent hairy skin for reconstructing auricular concave surfaces after Mohs surgery

Abstract: Background Reconstruction of large auricular defects with full‐thickness skin grafts (FTSG) is a commonly reported option, but less attention has focused on the advantages and indications of using split‐thickness skin grafts (STSG) in the ear. Objective We sought to report our experience using STSG for repair of defects located on the auricular concave surfaces, highlighting the utility of choosing the adjacent hairy skin as donor site. Methods We performed a retrospective review of all Mohs micrographic defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore for the reconstructions of the ear convex regions, as the helical rim, FTSGs represent an inadvisable choice for two reasons: first, they do not allow the volumetric replacement to restore the auricular contour and symmetry; second, it is difficult to ensure proper postoperative compression over the whole graft surface, making its survival unlikely 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore for the reconstructions of the ear convex regions, as the helical rim, FTSGs represent an inadvisable choice for two reasons: first, they do not allow the volumetric replacement to restore the auricular contour and symmetry; second, it is difficult to ensure proper postoperative compression over the whole graft surface, making its survival unlikely 24 …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore for the reconstructions of the ear convex regions, as the helical rim, FTSGs represent an inadvisable choice for two reasons: first, they do not allow the volumetric replacement to restore the auricular contour and symmetry; second, it is difficult to ensure proper postoperative compression over the whole graft surface, making its survival unlikely. 24 When there is the loss of cartilage support, the cartilage is deprived of the perichondrium or there is a major loss of the original auricular three-dimensionality, and local flaps represent the best option, since they can be associated with cartilage grafts.…”
Section: Discussionmentioning
confidence: 99%
“…At the 1-month follow-up visit, the donor site scar outcomes were evaluated by 2 board-certified dermatologists using the Vancouver Scar Scale (VSS) (Figure 2D). The VSS assess vascularity (normal [0], pink [1], red [2], purple [3]), pigmentation (normal [0], hypopigmentation [1], hyperpigmentation [2]), pliability (normal [0], supple [1], yielding [2], firm [3], ropes [4], contracture [5]), and height (flat [0], ,2 mm [1], 2-5 mm [2], . 5 mm [3]).…”
Section: Follow-upmentioning
confidence: 99%
“…However, for certain anatomical locations, such as the ear, STSG may be a simple and an excellent choice of repair. [1][2][3][4][5] When reviewing the literature, STGS are typically harvested from the thigh, forearm, inner upper arm, abdomen, and postauricular area. 1,2 To this date, no studies have evaluated the hair bearing scalp as a potential source for STSG harvesting.…”
mentioning
confidence: 99%
“…Skin grafts harvested from the retro-auricular and mastoid area have been described for reconstruction in cases of microtia, facial reconstruction and other otologic procedures. [6][7][8] Alam et al 9 found that approximately 1 in 5 cases of MMS involving the ear were reconstructed using a skin graft and that the auricular area was among the most common of all anatomical regions to be reconstructed using this method. Skin graft harvesting is a relatively simple reconstruction option that can be performed in a single stage, does not necessitate special instruments and is very cost-effective.…”
Section: Introductionmentioning
confidence: 99%